Scw10p, a cell-wall glucanase/transglucosidase important for cell-wall stability in Saccharomyces cerevisiae - Sestak, Sergej; Strahl, Sabine (Microbiology, 2004)
Glycosyl hydrolases and transferases are crucial for the formation of a rigid but at the same time plastic cell wall in yeasts and fungi. The Saccharomyces cerevisiae glucan hydrolase family 17 (GH17) contains the soluble cell-wall proteins Scw4p, Scw10p, Scw11p and Bgl2p. For Bgl2p, endoglucanase/glucanosyltransferase activity has been demonstrated, and Scw11p has been shown to be involved in cell separation. Here, Scw4p and Scw10p, which show 63% amino acid identity, were characterized. scw4 and scw10 single mutants were sensitive towards cell-wall destabilizing agents, suggesting a role in cell-wall assembly or maintenance. Simultaneous deletion of SCW4 and SCW10 showed a synergistic effect, and activated the cell-wall compensatory mechanism in a PKC1-dependent manner. Both the amount of cell-wall chitin and the amount of mannoproteins attached to chitin were increased in mutant scw4scw10. Deletion of CHS3 proved the critical role of chitin in scw4scw10. However, the mannoprotein Sed1p and the glucan synthase Fks2p were also crucial for cell-wall stability in mutant scw4scw10. The exchange of two conserved glutamate residues localized in the putative catalytic domain of GH17 family members strongly suggests that Scw10p acts as a 1,3-β-glucanase or as a 1,3-β-glucanosyltransferase. In addition, the synthetic interactions between Bgl2p and Scw10p which support a functional cooperation in cell-wall assembly were analysed. The data suggest that Scw4p and Scw10p act as glucanases or transglucosidases in concert with other cell-wall proteins to assure cell-wall integrity.